The relationship between training and development strategies, employee performance, and organizational performance - Wahyu Prabawati Putri Handayani; Didik Joko Pitoyo; Mugi Harsono (Sebelas Maret Business Review, 2020)
This study aims to analyze the influence of training and development strategies on organizational performance through mediating employee performance. This study involved 70 respondents from PT INKA Multi Solutions (IMS) level manager employees. The SPSS software is used to test the influence between variables. This study finds that training and development strategies have significant effect on organizational and employee performance. Moreover, this study also finds that employee performance mediates the influence of training and development strategies on organizational performance.